2020
DOI: 10.1128/aac.00456-20
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Isoniazid Is a Novel Mechanism of Isoniazid Resistance in Mycobacterium tuberculosis

Abstract: Isoniazid (INH), one of the first-line drugs used for tuberculosis treatment, is a pro-drug which is activated by the intracellular KatG enzyme of Mycobacterium tuberculosis. The activated drug hinders cell wall biosynthesis by inhibiting InhA protein. INH resistant strains of M. tuberculosis usually have mutations in katG, inhA, ahpC, kasA, and ndh genes. However, INH resistant strains which do not have mutations in any of these genes are reported, suggesting that these strains may adopt some other mechanism … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…In the present study, the putative acetyltransferase Rv2710 in MTB is reported to inactivate INH. The overexpression of Rv2710 in M. tuberculosis H37Ra leads to its resistance to INH at MICs [ 19 ].…”
Section: Lys Acylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the putative acetyltransferase Rv2710 in MTB is reported to inactivate INH. The overexpression of Rv2710 in M. tuberculosis H37Ra leads to its resistance to INH at MICs [ 19 ].…”
Section: Lys Acylationmentioning
confidence: 99%
“…The active INH Beta-ketoacyl-acyl carrier protein reductase (MabA) and NADH-specific enoyl acyl carrier protein reductase (InhA) are important enzymes associated with FAS-II [ 51 , 52 ]. The activated INH inhibits the InhA protein by binding to its active site which, in turn, hinders mycolic acid synthesis, and disturbs M. tuberculosis cell wall biosynthesis [ 19 ]. MabA and InhA can be phosphorylated by many kinds of STPKs, including PknB.…”
Section: Ser/thr/tyr Phosphorylationmentioning
confidence: 99%
“…e characterization of a novel series of the phenylisoxazole-3/5-carbaldehyde isonicotinylhydrazone derivatives 1-8 was performed by using the 1D NMR ( 1 H-and 13 C-NMR) and 2D ( 1 H-1 H COSY, 1 H-1 H NOESY, 1 H- 13 C HSQC, and 1 H- 13 C HMBC) spectra, recorded in acetone-d 6 / DMSO-d 6 (see Supplementary [11][12][13][14][15]18,19,22,23,26,[28][29][30][31][32][34][35][36][37][38]41,and 42 in Supplementary Materials).…”
Section: Nmr Spectramentioning
confidence: 99%
“…It is well known that the N-acetyltransferases (NATs) have been implicated in the resistance developed by "isoniazid, one of the first-line drugs in TB treatment" [1], due to the enzymatic acetylation of its primary amino group to form N-acetyl INH [2,[8][9][10][11][12]. In this sense, one of the benefits of isoniazid is obtaining a broad spectrum of novel isoniazid derivatives by condensing the terminal amine group (-NH 2 ) with the carbonyl group (-C�O) from aldehydes or ketones to produce new compounds with functional groups of the acylhydrazone type (∼CH�NH-NH-C�O∼) [13,14] that can act as bidentate ligands (N,O) and coordinate to transition metals to obtain bis-chelate complexes [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…If we classify drugs by activity, the most effective drugs are isoniazid (INH) and rifampicin (RIF). Isoniazid has been used since the beginning of the 20th century, and in some cases, MTB has mutated to become resistant to this drug, as it has to many other first-line drugs [7][8][9]. Multidrug resistance tuberculosis (MDR-TB)…”
Section: Introductionmentioning
confidence: 99%